Comparison of second and third generation parathyroid hormone (PTH) assays performed at Charlotte Maxeke Johannesburg Academic Hospital – Are they fit for purpose? - Nhlapo, Nokuthula (University of the Witwatersrand, Johannesburg, 2023)
Background: Parathyroid hormone (PTH) measurement is crucial in the investigation of calcium and phosphate disorders and in the management of chronic kidney disease (CKD). Available PTH assays include second (intact PTH) and third generation (PTH 1-84) assays. Intact PTH assays are widely available and used for clinical guidelines but overestimate PTH in CKD. PTH 1-84 assays are more specific, but lack of standardisation has complicated clinical interpretation. The study aimed to compare the second and third generation assays to determine the difference in analytical performance and the effect on clinical interpretation. Methods: A method comparison was done on 481 patient samples with PTH requested at Charlotte Maxeke Johannesburg Academic Hospital. PTH was measured in each sample using both intact PTH and PTH 1-84 assays. Passing Bablok regression and Bland Altman plots were performed to determine method agreement and bias. Analytical performance was assessed using the European Federation of Clinical Chemistry and Laboratory Medicine biological variation specifications. Clinical performance was compared in the diagnosis of hypo- and hyperparathyroidism, and in predialysis and dialysis CKD based on current Kidney Disease Improving Global Outcomes guidelines. Results: Intact PTH had a higher median concentration than PTH 1-84 (9.93 vs 8.60 pmol/L, p<0.0001) but showed good correlation (r = 0.994 and p<0.0001). Regression analysis revealed significant systematic and proportional differences, with increased deviations at higher concentrations. The average bias was above allowable bias of 7.1%. Clinical interpretation of hypo- and hyperparathyroidism and predialysis and dialysis groups was unchanged. Conclusions: There was significant bias observed between the two PTH assays thus, they should not be used interchangeably. However, no significant changes in clinical interpretation were found when one assay was used over the other. The decision to use third over second generation PTH assay should consider the impact on clinical interpretation in the population.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Medicine in Chemical Pathology, to the Faculty of Health Sciences, School of Pathology, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Parathyroid hormone (PTH); Second generation PTH assays (Intact PTH); Third generation PTH assays (PTH 1-84); Chronic kidney disease (CKD); Charlotte Maxeke Johannesburg Academic Hospital; European Federation of Clinical Chemistry and Laboratory Medicine; Kidney Disease Improving Global Outcomes guidelines; UCTD; SDG-3: Good health and well-being; SDG-4: Quality education